Intensi Wisatawan Berkunjung Kembali ke Agrowisata: Perspektif Afektif dan Kognitif (Studi Kasus New Agro Rekadena) - Muhammad Chaikal Alfikri; Eva Dolorosa; Anita Suharyani (Mimbar Agribisnis : Jurnal Pemikiran Masyarakat Ilmiah Berwawasan Agribisnis, 2026)
Agritourism is a tourist activity that utilizes the agricultural sector as a tourist object and is a tourism sector that has the potential to be developed in Indonesia. The intention of tourists to visit again has an important role to maintain the agritourism business, the intention of tourists to visit again can be influenced by various factors including affective and cognitive factors. This study aims to look at the intention of tourists to visit again from an affective and cognitive perspective. The location of this research was conducted at New Agro Rekadena which is located on Jl. Jeruju Laut, Jeruju Besar Village, Sungai Kakap District, Kubu Raya Regency. This research began in August to December 2023. This research method uses the SEM (Structural Equation Modeling) analysis method to analyze primary data obtained by distributing questionnaires to 96 tourists who have visited New Agro Rekadena at least 2 times. The results of this study indicate that affective and cognitive factors have a significant effect on tourist intention to visit again.